Tourism Digitalization Through the Implementation of National Tourism Information System “Sisparnas” in Papua Province - Oscar Oswald O. Wambrauw; Ilham (East Asian Journal of Multidisciplinary Research, 2023)
The study discusses the digitization of tourism with a focus on the Implementation of the National Tourism Information System (Sisparnas) in Papua Province. The method used is a library research approach. The results of this study indicate that the tourism competitiveness index for Papua is still low, at 30 (thirty) out of 34 (thirty-four) provinces in Indonesia. Furthermore, updating the Sisparnas data was carried out by involving a team of surveyors who served in five customary areas. The surveyor team is equipped through the implementation of technical guidance to provide education on the importance of data and information in order to develop tourism. As a recommendation for engagement, the surveyor should not only see from the perspective of experience in the field of tourism but also understand the conditions and situation of the area as well as the tourism potential of the area, therefore, it is better for the surveyor team to come from representatives of each regency or city.